Crisis of social knowledge and rescue of the moral and ethical subject in times of globalization - Villa Becerra, Irene (2006)
The article starts from some conceptual precisions around the implicit epistemological bases in the task of social knowledge. Its objective is to determine the two great challenges that, in my opinion, would constitute the central problems of the contemporary debate in the context of postmodernity and globalization: on the one hand, the changes and new epistemological visions to address the crisis of the rationality of social knowledge and its reconstruction; on the other hand, how to address, manage and rescue the loss of the foundation of ethics.